The influence of incentives, job motivation, and job satisfaction on performance of offices of danau kerinci district - Wazirman Wazirman; Nurmawati Nurmawati; Pretti Pretti; Yandi Yandi (Education and Social Sciences Review, 2022)
This study aims to see the effect of (1) Incentives for the performance of the employees of the Danau Kerinci sub-district office (2)Work motivation on the performance of the employees of the Danau Kerinci Sub-District Office (3) Job satisfaction on the performance of the employees of the Danau Kerinci District Office (4) Incentives, work motivation and job satisfaction have a joint effect on the performance of the employees of the Danau Kerinci Sub-District Office. The population in this study is allThere are 30 employees of the Danau Kerinci Sub-district Office. Techniques for determining the number of samplesusing total sampling.The results of this study indicate that (1) Incentivehas a positive significant effect on the performance of the employees of the Danau Kerinci Sub-district Office (2) Work motivationprovide a positive influence on the performance of the employees of the Danau Kerinci Sub-district Office (3) Job satisfactionprovide a positive influence on the performance of the employees of the Danau Kerinci Sub-district Office (4) Incentives, work motivation and job satisfactionjointly have a positive effect on the performance of the employees of the Danau Kerinci District Office